Are We Really Monotheists? - Nida, Eugene Albert (Practical anthropology, 1959)
The Christian doctrine of the Trinity is a puzzling one for missionaries who try to explain it — or understand it, for that matter. In this article Dr. Nida discusses the mental images of the Trinity which we often carry around with us and try to teach to others. The response in those “others,” if they are Muslims, should well give us pause and make us stop to consider just what we do say and think.